CONTINUOUS INTRAVENOUS NIMODIPINE APPLICATION FOR PREVENTION OF VASOSPASM BEFORE ENDOVASCULAR TREATMENT OF RUPTURED CEREBRAL ANEURISMS - Bushinoska, Jasna M.; Chaparoski, Aleksandar; Lazareska, Menka; Bushinoska-Ivanova, Gabriela; Ognjenovic, Ljubomir; Kostov, Milenko; Asani, Elmedina; Zafirova, Dina; Vesova, Marija (Journal of Morphological Sciences, 2022)
Early recognition of vasospasm (VS) in patients with aneurismal subarachnoid hemorrhage (aSAH) is an imperative for timely treatment and prevention of delayed cerebral ischemia (DCI). VS, the pathologic response of the vascular damage in aSAH, is the main risk factor for irreversible brain damage. The first step in successful solving of aneurismal bleeding is prevention and treatment of VS. The aim of this study is to determine whether medical treatment with continuous infusion of intravenous Calcium blocker Nimodipine, without radiology verified VS will impact the degree of arterial vasoconstriction during the endovascular aneurismal treatment (EVT). A total of 20 patients with aSAH, confirmed by CT-angiography and hospitalized in UC for Neurosurgery were included in the study. In 10 patients, a continuous iv Nimodipine infusion was initiated on admission, the other half remained on their own antihypertensive therapy. If signs of VS or neurologic deterioration had developed, iv vasodilator therapy would have been initiated. Control angiography and immediate EVT were performed on the 4 th day of admission at Radiology Institute. Using angiography, the vascular diameter was measured and compared with the same vessel diameter on CTA, to determine whether iv Nimodipine is effective in the pretreatment period. In 8 of 10 treated patients with iv Nimodipine, VS resolved in preEVT period. Among the patients from the non-treated group, 1 had developed DCI, 1 had no VS, 6 had persistent and in 2 patients VS resolved spontaneously. The conclusion is that continuous iv Nimodipine in preEVT period has vasodilatory potency on the vascular pool. Key words: Aneurismal subarachnoid hemorrhage, vasospasm, intravenous Nimodipine, endovascular treatment